Desirable characteristics of the teacher in sciences in the framework of the methodology of the inquiry in the regional of Guápiles Costa Rica (Revista Electrónica Calidad en la Educación Superior, 2019)
Teaching requires qualities and characteristics that facilitate the promotion of skills, competences, attitudes and knowledge, in order to captivate the students in their learning process. With the aim of characterizing the professor in teaching Sciences, this investigation was performed to have an approach and starting point with the profiles proposed by the MEP in the new study programs of Sciences, based on the methodology of the exploration. The 25 teacher focus group with 79 eleventh grade students surveyed was applied as the data collection techniques. The results highlighted as desirable characteristics of the teacher: the vocation to teach, understand the student, content management, diversification of strategies that promote exploration, analysis and reflection of what is intended, motivation among others is important according to teachers and students. In conclusion, the teacher must not be a passive subject or transmitter of knowledge as absolute truth, but rather a facilitator of this process, where the student is considered an architect and builder of his own knowledge.
Keywords: Students; teacher; exploration; classroom; learning; science